2015
DOI: 10.1007/s00299-015-1769-x
|View full text |Cite
|
Sign up to set email alerts
|

Inside out: high-efficiency plant regeneration and Agrobacterium-mediated transformation of upland and lowland switchgrass cultivars

Abstract: Selection of pre-embryogenic callus from a core structure from mature seed-derived callus is the key for high-efficiency plant regeneration and transformation of switchgrass different cultivars. Switchgrass (Panicum virgatum L.) has been identified as a dedicated biofuel crop. For its trait improvement through biotechnological approaches, we have developed a highly efficient plant regeneration and genetic transformation protocol for both lowland and upland cultivars. We identified and separated a pre-embryogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
66
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 29 publications
2
66
0
Order By: Relevance
“…Transgenic plants were obtained in all tested callus lines of two lowland cultivars, ' Alamo' and 'Kanlow' , at comparably higher efficiency than that achieved in previous reports using Type I callus. The transformation efficiency of one ' Alamo' line, A11-01, was as high as 59.2%, which was comparable to the previously reported efficiency for Type II callus of ' Alamo' at 56.6% by Li and Qu (2011) and 72.8% by Liu et al (2015). In addition, we successfully transformed the upland cultivar 'Trailblazer' using the present method.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Transgenic plants were obtained in all tested callus lines of two lowland cultivars, ' Alamo' and 'Kanlow' , at comparably higher efficiency than that achieved in previous reports using Type I callus. The transformation efficiency of one ' Alamo' line, A11-01, was as high as 59.2%, which was comparable to the previously reported efficiency for Type II callus of ' Alamo' at 56.6% by Li and Qu (2011) and 72.8% by Liu et al (2015). In addition, we successfully transformed the upland cultivar 'Trailblazer' using the present method.…”
Section: Discussionsupporting
confidence: 83%
“…Albino shoot formation from Type II callus was also reported by Ramamoorthy and Kumar (2012). Very recently, Liu et al (2015) reported efficient induction and transformation methods of Type II calli in coupled with the discovery of "shell-core" structure. They achieved 72.8% of transformation efficiency for a lowland cultivar ' Alamo' , and successfully obtained first transgenic plants of an upland cultivar 'Dacotah' .…”
mentioning
confidence: 67%
See 3 more Smart Citations